Predicting Adverse Health Outcomes in Older Patients Presenting to the Emergency Department: The Acutely Presenting Older Patient Study. (19th April 2017) - de Gelder, Jelle; Lucke, Jacinta A.; de Groot, Bas; Fogteloo, Anne J.; Anten, Sander; Mesri, Kanar; Steyerberg, Ewout W.; Heringhaus, Christian; Blauw, Gerard J.; Mooijaart, Simon P.
Abstract : Background: Older patients experience high rates of adverse outcomes after an emergency department (ED) visit. Early identification of those at high risk could guide preventive interventions and tailored treatment decisions, but available models perform poorly in discriminating those at highest risk. This study aims to develop and validate a prediction model for functional decline and mortality in older patients presenting to our ED. Methods: A multicenter prospective follow‐up study in EDs of the Leiden University Medical Center (LUMC; derivation) and Alrijne Hospital (validation) was conducted. All presenting patients aged 70 and over were included during 12 weeks for 7 days per week. A baseline assessment shortly (<1 hour) after presentation included demographics, severity of disease indicators, and measurements of functional and cognitive impairment. The main outcomes were a composite of functional decline or mortality after 90 days and mortality separately. Results: In total 751 patients were included in the LUMC of whom 230 patients (30.6%) experienced the composite adverse outcome and 71 patients (9.5%) died. The final model for the composite adverse outcome resulted in an area under the curve (AUC) of 0.73 (95% CI = 0.67–0.77) and was experienced in 69% of the patients at highest risk. For mortality the AUC was 0.79 (95% CI = 0.73–0.85) and 36% of the patients at highest risk died. External validation in 881 patients of the Alrijne Hospital showed an AUC of 0.71 (95% CI = 0.67–0.75) for the composite adverse outcome and 0.69 (95% CI = 0.63–0.75) for mortality. Conclusion: We successfully developed and validated prediction models for 90‐day adverse outcomes and 90‐day mortality in older emergency patients. The benefits for patients by implementing these models with preventive interventions must be investigated.